The Status of Quality Assurance in Two Lebanese Universities - Al Chibani, Wessam (Pedagogika, 2016)
This study was set to assess and analyze the status of two private university quality measures such as the quality audit, control, and ranking in Lebanon. In addition, it was set to discuss and evaluate the programs given by these universities. Finally, it was set to synthesize and analyze different tools that could be applied on the quality services these universities have. The sample of this study is two private universities in Lebanon where interviews were conducted separately with 6 deans, 6 chairpersons, and 6 coordinators. In addition to the universities, plenty of information was taken directly from the Ministry of Education and Higher Education of the Republic of Lebanon. Thus, qualitative data analyses were conducted. Main results showed that one of the main aims of both universities is to get new students registered and have better quality of education. They always take into consideration the quality audit, control, and ranking, which allow them to be ranked from the top universities in Lebanon. One University has been accredited in 2015, which makes it necessary to follow up with the quality control; the second university is still working on getting accredited. The study concluded with recommendations addressed to private universities in Lebanon.